Pengembangan Media Pembelajaran Interaktif dengan Menggunakan Software Swishmax pada Materi Segiempat Kelas VII SMP - Maulana, Hutomo Atman (Universitas Islam Negeri Imam Bonjol Padang, 2017)
This study wa research and development. This study aimed to develop an interactive learning media for rectangular in 7 th grade by using Swishmax and to know the effect of the media on the student learning outcomes. This study adapted ADDIE development model that consist of five steps: analysis, design, development, implementation, and evaluation. The instruments used in the form of media evaluation that were given to a lecturer as material expert, an IT practioner as media expert, and questionnaire sheet for knowing student’s feedback. The implementation stage was conducted for 35 students of class VII.1 SMP Negeri 10 Jambi. As a result in evaluation stage obtained 93.93% students passed the 65 minimum passing grade which based on analysis of the final test and 78.78% students gave positive feedback to the application of the development product.